Control Led Through Internet Based On Nodemcu With Blynk Application - Asmawati, Ari; Putra, Fajar Januar Eka; Richie, Leonel (Pandawan, 2019)
Internet (interconnected-networking) is a series of computers that are connected globally in several circuits and use TCP / IP as packet exchange communication protocol. The internet as part of the technological development that is very rapidly developing in people's lives today has been able to be used as a medium of communication and control of devices from a distance as long as they are still connected to each other. The internet is like virtual threads that connect with one another, forward data and convey data from one point to another. However, along with the development of increasingly advanced science and technology, the internet is no longer just to connect between humans but also to control between any object that can be connected. In this study there were 3 (three) problems and 3 (three) problem solving methods Electronic device control in the form of LED lights using an IoT platform that is open source. This study uses the NodeMCU module as a station, which will be controlled by the Blynk application with an internet connection. In this study using the NodeMCU module as a station, which will be controlled by the Blynk application by connecting to the internet.